Less-lampblack wear-resistant non-stick pan and manufacturing method
By adopting a multi-layer structural design on the non-stick pan, including antibacterial anti-stick layer and pot body layer, the problems of easy damage to the non-stick layer, poor thermal conductivity and high oil fume are solved, and the wear resistance, thermal conductivity and reduced oil fume are improved, ensuring service life and food safety.
Patent Information
- Application Number
- CN202411641620.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-14
AI Technical Summary
The non-stick layer of existing non-stick pans is prone to damage, has poor thermal conductivity, short service life, and is prone to produce a large amount of oil smoke when cooking.
The multi-layer structural design of the antibacterial anti-adhesive layer and the pot body layer is adopted. The antibacterial anti-adhesive layer consists of a nanodiamond coating and a titanium ion nanosilver ion composite layer. The pot body layer is composed of tungsten steel alloy, thermally conductive copper and chromium alloy layers, and is precision processed and assembled on the pot body and handrail assembly.
It improves the wear resistance and thermal conductivity of the non-stick pan, extends the service life, reduces the generation of oil fume, and provides efficient antibacterial properties, ensuring the safety and hygiene of food.
Smart Images

Figure CN119606174A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of non-stick pans, in particular to a smoke-free, wear-resistant non-stick pan and a manufacturing method thereof. Background Art
[0002] A non-stick pan is a cooking utensil with a special coating, usually a pot, such as a wok or frying pan. Its core feature is its non-stick performance, which is mainly due to the coating on the inner surface of the pan. Common coatings include polytetrafluoroethylene (PTFE) and ceramic coatings.
[0003] The common non-stick pan coating is usually a conventional polytetrafluoroethylene coating process, which has a low hardness. The non-stick coating is easily scratched when cooking with a spatula, which affects the service life of the non-stick pan. In addition, the high temperature in the pan when cooking with a non-stick pan easily produces a lot of oil smoke.
[0004] The Chinese patent with the announcement number "CN217610679U" discloses a novel antibacterial non-stick pan, which includes a non-stick pan body, a pan handle, a pan cover, a first hanging ring, a second hanging ring and a connecting rod. When the above device is hung, the height of the non-stick pan body can be adjusted arbitrarily, which is convenient for taking. The non-stick pan body is erected, and the first hanging ring and the second hanging ring are placed on the stove, so that the non-stick pan body can be supported without an additional placement rack. The residual water in the pan can flow down along the curved surface of the non-stick pan body, which is convenient for the non-stick pan body to dry quickly.
[0005] Obviously, the structure of the above-mentioned non-stick pan has certain limitations. During specific application, the overall thermal conductivity of the pan body layer is relatively poor, making it difficult to achieve fast and uniform heating. Moreover, the conventional process of coating polytetrafluoroethylene coating has obvious deficiencies in daily use. The hardness of the non-stick layer is low, and it is very easy to be scratched and damaged during use. Once the non-stick layer is damaged, the pan is prone to sticking, and it will also cause the generation of oil smoke. In addition, the overall hardness and thermal conductivity of existing non-stick pans are relatively general, which cannot meet people's demand for high-quality cooking utensils. Therefore, in order to improve the performance and service life of non-stick pans, it is urgently necessary to improve and perfect them. Summary of the invention
[0006] The object of the present invention is to provide a less smoke and wear-resistant non-stick pan and a manufacturing method thereof, so as to solve the problems in the above-mentioned background technology that the non-stick layer of the existing non-stick pan is easily damaged and the overall heat conduction and use strength thereof are poor.
[0007] To achieve the above-mentioned object, the present invention provides a low-smoke wear-resistant non-stick pan and a manufacturing method thereof, comprising a non-stick pan body, wherein the non-stick pan body is composed of an antibacterial anti-stick layer and a pan body layer, wherein the antibacterial anti-stick layer is fixedly connected to the outer side of the pan body layer, and a handrail assembly is fixedly connected to one side of the non-stick pan body;
[0008] The pot body layer comprises a base layer, the base layer is arranged at the bottom of the non-stick body, the top of the base layer is fixedly connected to a heat-conducting layer, and the top of the heat-conducting layer is fixedly connected to a base-top layer.
[0009] Furthermore, the base layer is configured as a tungsten steel alloy layer, and the heat conducting layer is configured as a heat conducting copper layer.
[0010] Furthermore, the base and top layers are configured as chrome alloy layers, the cross-sectional shapes of both ends of the non-stick pan body are configured as arc shapes, and the top corners of the non-stick pan body are also configured as arc shapes.
[0011] Furthermore, the antibacterial and anti-sticking layer comprises a non-stick layer, the non-stick layer is fixedly connected to the top of the base layer, and the top of the non-stick layer is fixedly connected to a composite antibacterial layer.
[0012] Furthermore, the non-stick layer is provided with a nano-diamond coating, and the composite antibacterial layer is provided with a titanium ion and nano-silver ion composite layer.
[0013] Furthermore, the armrest assembly includes an armrest frame, which is integrally formed and fixedly connected to one side of the non-stick pan body, and the outer end of the armrest frame is integrally formed and fixedly connected to a handrail rod, and a wooden handle is installed on the outer side of the handrail rod by bolts.
[0014] Furthermore, the wooden handle is generally cylindrical in shape, and annular anti-slip grooves are provided at equal intervals on the outer surface of the wooden handle.
[0015] A method for manufacturing a low-smoke, wear-resistant, non-stick pan, comprising the following steps:
[0016] S1: base layer processing, material preparation, select tungsten steel alloy with hardness between HRC80-90, strictly control the impurity content below 0.1%, determine the amount of tungsten steel alloy required according to the size of the pot, use precision casting or forging process, control the temperature at 1500-1700℃ during casting, so that the tungsten steel alloy is fully melted and flows into the mold to shape the bottom of the pot, and the forging temperature is controlled at 1200-1400℃. Through repeated hammering and extrusion, the density and uniformity of the material are improved to ensure that the bottom of the pot is flat and the thickness meets the design requirements. The thickness range can be 2-4 mm, and the size deviation is controlled within ±0.2 mm;
[0017] S2: For heat-conducting layer processing, high-purity copper materials are selected, and the thermal conductivity is between 380-400W / (m·K). The thickness of the copper layer is determined according to the size of the pot and the design requirements. The specific thickness range is 0.5-1.5 mm. Electroplating or hot-dip plating is selected. When electroplating, the current density is controlled at 2-5A / dm 2The temperature is maintained at 30-50℃, so that the copper ions are evenly deposited on the tungsten steel alloy base layer. The hot dip plating is carried out at a high temperature of 800-1000℃ to ensure that the copper layer is closely bonded to the base layer, and the bonding strength is greater than 15MPa.
[0018] S3: For base and top layer processing, select chromium alloy with hardness between HRC50-60, and then determine the required amount of chromium alloy, with a thickness of 0.5-1 mm. Welding or spraying can be used during processing. If welding is used, the welding temperature is controlled at 1000-1200℃. The welding current is accurately determined according to the thickness of the chromium alloy and the welding method to ensure that the welding is firm. If spraying is used, the spraying pressure is controlled at 0.3-0.5MPa, and the spraying distance is maintained at 150-200mm, so that the chromium alloy is evenly covered on the thermal conductive copper layer to ensure that the chromium alloy layer and the copper layer are firmly bonded, and the bonding strength is greater than 10MPa;
[0019] S4: Non-stick layer processing, select nano diamond powder with a particle size between 10-50 nanometers, and use advanced PVD or CVD methods for coating. If PVD processing is used, the deposition temperature is 300-500℃ and the vacuum degree is 10 -3 -10 -4 Pa high vacuum environment, the nano-diamond particles are uniformly deposited on the top layer of the chromium alloy base, the CVD reaction temperature is 800-1000 ° C, the reaction pressure is 1-10kPa, and a dense nano-diamond coating is generated through chemical reaction, and the coating thickness is controlled at 0.01-0.05 mm;
[0020] S5: Composite antibacterial layer processing, prepare materials with titanium ion particle size between 50-100 nanometers and nano silver ion particle size between 10-30 nanometers, and use coating process to form a composite antibacterial layer.
[0021] S6: Handrail assembly processing, using stainless steel alloy that matches the material of the cookware, with a hardness between HRC30-40, through mold casting or machining, the handrail frame and handrail rod are integrally formed to ensure that the shape is regular and the size meets the design requirements. The connection between the handrail frame and the cookware should be finely processed to ensure a firm connection. Then, natural wood such as oak, walnut, etc. is selected, dried and anti-corrosion treated, and the wood is processed into a cylindrical shape. The outer surface is provided with annular anti-slip grooves at equal intervals, with a thickness of 10-20 mm and a length that matches the handrail rod;
[0022] S7: Assemble, install the wooden handle on the outside of the handrail with bolts, select bolts of appropriate specifications, strictly control the tightening force, ensure that the installation is firm and there is no looseness, and then fix the handrail frame to one side of the non-stick pan body in one piece. The connection parts are welded or other reliable connection methods to ensure that the connection is firm and there are no cracks or unevenness;
[0023] S8: Quality inspection, appearance inspection: Carefully check the overall appearance of the cookware, including the pot body and the armrest assembly, to ensure that the surface is smooth, without scratches, dents and other defects, the coating color and glossiness are uniform, the wooden handle surface is flawless, and the annular anti-slip groove is clear and regular;
[0024] Dimension detection: Use calipers, micrometers and other precision tools to measure the size of the cookware, including diameter, depth, and size of the armrest assembly. The diameter deviation is controlled within ±1 mm, the depth deviation is controlled within ±0.5 mm, and the size deviation of the armrest assembly is controlled within a reasonable range;
[0025] Performance testing: thermal conductivity test of the cookware, heat the cookware to a certain temperature, measure the temperature change at different positions, ensure that the thermal conductivity is greater than 100W / (m·K), non-stick performance test, observe the adhesion of food by cooking, which must meet the national standard requirements, antibacterial performance test, inoculate bacteria and measure the change in quantity, ensure that the antibacterial rate is greater than 99%, strength test of the handle, apply a certain force to check deformation and firmness, and require it to withstand a tensile force of at least 50N;
[0026] Overall stability check: Check the stability of the connection between the cooker and the armrest assembly. Lift the cooker and gently shake it to check if it is loose or makes unusual noises to ensure that the cooker is safe and reliable during use.
[0027] Furthermore, the processing of the composite antibacterial layer includes the following steps:
[0028] 1): Pretreatment of the base material, the processed pot body layer is treated, chemical cleaning can be used during the treatment, specifically, ethanol organic solvents, acetone and the like are used to soak the base material to remove the oil on the surface, and then dilute hydrochloric acid or dilute sulfuric acid is used to remove impurities such as oxides. During the cleaning process, appropriate heating and stirring can be performed to improve the cleaning effect. The cleaning time depends on the degree of contamination of the base material, which is 10-30 minutes. Physical cleaning can also be used, specifically, ultrasonic cleaning of the base material after chemical cleaning, placing the base material in an ultrasonic cleaning tank, adding an appropriate amount of distilled water or deionized water cleaning solution, and turning on the ultrasonic cleaning machine. The cleaning time is 10-20 minutes. Ultrasonic cleaning can further remove tiny impurities on the surface of the base to ensure that the surface is flat and clean;
[0029] 2): PVD process, put the pre-treated substrate into the vacuum chamber of the PVD equipment, ensure that the substrate is placed stably and maintains good contact with the electrodes and other components in the chamber, start the vacuum pump, evacuate the vacuum chamber, and gradually reduce the pressure to 10 -3 -10 -5 Pa, this process may take some time, depending on the performance of the vacuum pump and the size of the chamber;
[0030] At the same time, the sputtering power of the titanium target and the silver target is turned on, and the sputtering power is adjusted according to the required ratio of titanium ions and nano silver ions. The power of the titanium target can be set at 3-5kW, and the power of the silver target can be set at 1-3kW. At the same time, a proper amount of argon gas is introduced into the chamber, and the flow rate is controlled at 20-50sccm. The argon gas forms argon ions under the action of the electric field, bombarding the titanium target and the silver target, so that the titanium ions and the silver ions are sputtered out;
[0031] During the deposition process, the uniformity of the coating is ensured by controlling the rotation speed of the substrate. The rotation speed of the substrate is set to 5-10rpm. Depending on the required coating thickness, the deposition time is 30-90 minutes. During the deposition process, the growth of the coating can be observed in real time through monitoring equipment in order to adjust the process parameters.
[0032] After the deposition is completed, turn off the sputtering power supply and gas supply, wait for the chamber pressure to return to atmospheric pressure, take out the substrate material, and perform quality inspection on the coating, specifically thickness measurement, surface roughness inspection, and adhesion test;
[0033] 3): Preparation of titanium sol, dissolving titanium alkoxide, which can be tetrabutyl titanate Ti(OBu)4, in an ethanol organic solvent at a ratio of 1:10, adding appropriate amounts of water and hydrochloric acid catalyst to the solution, wherein the amount of water added can be set to a molar ratio of tetrabutyl titanate, water and hydrochloric acid of 1:2:0.1, stirring evenly, stirring at room temperature for reaction, the stirring speed can be controlled at 200-400 rpm, the reaction time is 2-4 hours, until a transparent and stable sol is formed, during the reaction, the color and transparency changes of the sol can be observed to determine the progress of the reaction;
[0034] 4): Preparation of silver sol, using silver nitrate as a silver source, dissolving a certain amount of silver nitrate in water, adding an appropriate amount of glucose reducing agent and polyvinyl pyrrolidone PVP protective agent to the solution, the mass ratio of silver nitrate, glucose and PVP can be 1:0.5:1, reacting under heating and stirring conditions, controlling the temperature at 60-80°C, stirring speed at 300-500rpm, reaction time of 1-2 hours, during the reaction process, observing the color change of the solution, when the solution changes from colorless to light yellow or brown, indicating that nanosilver particles have been formed; after completion, cooling to room temperature to obtain silver sol, and performing quality inspection on the silver sol, specifically particle size distribution measurement and stability test;
[0035] 5): Sol-gel composite coating and heat treatment, the prepared titanium sol and silver sol are mixed in a 1:1 ratio, stirred evenly, and the mixed sol is coated on the substrate surface by dipping, spraying or spin coating according to needs. After coating, the substrate material is placed at room temperature to dry naturally for 1-2 hours, and then the substrate material is placed in an oven for heat treatment, the temperature is controlled at 100-200 ° C, and heated for 30-60 minutes. The heat treatment can gel the sol to form a composite coating; if the thickness of the coating needs to be increased, the coating and heat treatment process can be repeated. Before each coating, ensure that the previous coating has been completely dried and cured, and perform quality inspection on the composite coating, specifically thickness measurement, surface hardness test, and antibacterial performance test.
[0036] Furthermore, the composite antibacterial layer can also be processed by CVD process, specifically, the pretreated substrate is placed in the reaction chamber of the CVD equipment, and the reaction chamber door is closed to ensure good sealing;
[0037] Start the heating system and heat the reaction chamber to a suitable reaction temperature. For the composite deposition of titanium and silver, the temperature is controlled between 500-800°C. The heating process should be carried out slowly to avoid stress or deformation of the substrate material due to rapid temperature changes;
[0038] A titanium source and a silver source precursor gas, as well as a reducing gas, are introduced into the reaction chamber, titanium tetrachloride and silver nitrate are heated and evaporated respectively, and then introduced into the reaction chamber together with hydrogen, and the gas flow rate is adjusted according to the stoichiometric ratio of the reaction and the deposition rate requirements. The flow rate of titanium tetrachloride can be 10-30 ml / min, the flow rate of silver nitrate vapor can be 5-15 ml / min, and the flow rate of hydrogen can be 30-60 ml / min;
[0039] During the reaction process, the precursor is fully reacted and deposited on the substrate by controlling the pressure of the reaction chamber and the residence time of the gas. The pressure of the reaction chamber is controlled at 1-10 kPa, and the deposition time is 60-120 minutes to ensure that the composite coating thickness reaches 1-2 μm.
[0040] After the reaction is completed, turn off the heating system and gas supply, wait for the reaction chamber to cool to room temperature, take out the substrate material, and conduct quality inspection on the coating, specifically component analysis, crystal structure inspection, and surface morphology observation.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] First, in the present invention, the non-stick pan adopts a series of advanced manufacturing processes, including precision casting, forging, electroplating, hot-dip plating, PVD, CVD and sol-gel method, etc. These processes ensure the close combination, uniform distribution and high dimensional accuracy of each layer of materials. For example, in the processing of the base layer, the casting and forging temperatures are strictly controlled, so that the tungsten steel alloy base layer has excellent strength and wear resistance, and can withstand the external force impact in various cooking processes. The electroplating and hot-dip plating processes of the heat-conducting layer make the copper layer firmly combined with the base layer, efficiently conduct heat, shorten the cooking time and save energy. The various coating processes of the non-stick layer and the composite antibacterial layer ensure the quality and performance of the coating. For example, the PVD process makes the nano-diamond coating uniform and dense, and the non-stick performance is excellent; the composite antibacterial layer prepared by the sol-gel method has a significant antibacterial effect, and the strict quality inspection process further ensures that each pot meets the high quality standards, and is strictly checked from appearance to performance, providing users with reliable cooking tools;
[0043] Secondly, in the present invention, the pot body layer is composed of a base layer, a heat conductive layer and a base top layer. The careful selection of materials for each layer gives the pot excellent performance. The base layer is made of tungsten steel alloy with high hardness and few impurities, which lays a solid foundation for the pot and prolongs its service life. The heat conductive layer is made of high-purity copper material with high thermal conductivity to ensure uniform heating during cooking, avoid local overheating or overcooling, and improve cooking effects. The chromium alloy of the base top layer has good wear resistance and corrosion resistance, and protects the surface of the pot. At the same time, the arc-shaped design of the pot body layer is not only beautiful, but also increases the safety of use, avoiding possible injuries caused by sharp edges and corners. The reasonable design of the overall structure makes the pot excellent in strength, thermal conductivity, durability, etc., meeting the needs of users for high-quality pots.
[0044] Third, in the present invention, the antibacterial anti-stick layer is composed of a non-stick layer and a composite antibacterial layer. The non-stick layer adopts a nano-diamond coating with a particle size of 10-50 nanometers. The coating is fine and uniform, so that food is not easy to stick during the cooking process, and the cleaning is convenient and quick. At the same time, the nano-diamond coating has excellent wear resistance and high temperature resistance, and can maintain a non-stick effect for a long time. The composite antibacterial layer is composed of titanium ions and nano-silver ions, and is formed by a variety of processes. The antibacterial rate is greater than 99%. The synergistic effect of titanium ions and nano-silver ions effectively inhibits the growth and reproduction of bacteria. Nano-silver ions have high-strength antibacterial ability, and titanium ions have antibacterial ability and strong hardness, which can ensure high-strength antibacterial performance while maintaining its use strength, providing users with a safe and hygienic cooking environment. The presence of the antibacterial anti-stick layer not only improves the use experience of the cookware, but also protects the health of the family, which is one of the important advantages of this non-stick pan.
[0045] Fourthly, the pot body layer is composed of a base layer, a heat conductive layer and a base top layer. The reasonable design of the overall structure makes the pot perform well in terms of strength, thermal conductivity, durability, etc. This structural design can better maintain the stability of the temperature in the pot and avoid excessive temperature fluctuations that cause oil smoke. At the same time, the arc-shaped design is not only beautiful and generous, but also increases the safety of use, and to a certain extent helps to reduce the generation of oil smoke. The arc-shaped pot body layer can make the heat more evenly distributed in the pot, reduce the turbulence of the air flow, and thus reduce the generation of oil smoke. The non-stick layer uses a nano-diamond coating to prevent food from sticking during the cooking process. When the ingredients are not easy to stick, there is no need to stir and stir too much, thereby reducing the friction between the ingredients and the pot body layer and the excessive concentration of heat, thereby reducing the generation of oil smoke. Moreover, the nano-diamond coating has excellent high temperature resistance and can withstand high cooking temperatures without producing harmful substances, further reducing the generation of oil smoke. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 It is a schematic diagram of the overall structure of the present invention;
[0047] Figure 2 It is a schematic diagram of the top view structure of the present invention;
[0048] Figure 3 It is a schematic diagram of the structure in the present invention when viewed from above;
[0049] Figure 4 It is a side view structural schematic diagram of the present invention;
[0050] Figure 5 This is a schematic diagram of the structure of the handrail assembly in the present invention;
[0051] Figure 6 It is a schematic diagram of the cross-sectional structure of the pot body layer in the present invention;
[0052] Figure 7 Schematic diagram of the cross-sectional structure of the antibacterial anti-adhesive layer in the present invention;
[0053] Figure 8 The flowchart of the present invention is prepared.
[0054] In the figure: 1. non-stick pan body; 2. antibacterial and anti-stick layer; 21. non-stick layer; 22. composite antibacterial layer; 3. armrest assembly; 31. armrest frame; 32. armrest rod; 33. wooden handle; 34. annular anti-slip groove; 4. pan body layer; 41. base layer; 42. heat conductive layer; 43. base top layer. DETAILED DESCRIPTION
[0055] Example
[0056] See also Figure 1-Figure 8In an embodiment of the present invention, a low-smoke wear-resistant non-stick pan and a manufacturing method thereof include a non-stick pan body 1, the non-stick pan body 1 is composed of an antibacterial anti-stick layer 2 and a pan body layer 4, the antibacterial anti-stick layer 2 is fixedly connected to the outer side of the pan body layer 4, and a handrail assembly 3 is fixedly connected to one side of the non-stick pan body 1;
[0057] The pot body layer 4 includes a base layer 41, which is arranged at the bottom of the non-stick pan body. A heat-conducting layer 42 is fixedly connected to the top of the base layer 41, and a base-top layer 43 is fixedly connected to the top of the heat-conducting layer 42. The pot body layer 4 has a reasonable structural design. The base layer 41 adopts a specific material and process to ensure the high strength and durability of the pot, and can effectively resist wear and deformation in daily use. The setting of the heat-conducting layer 42 makes the pot have excellent thermal conductivity, can heat quickly and evenly, and saves cooking time and energy consumption. The base-top layer 43 further enhances the wear resistance and corrosion resistance of the pot. The antibacterial and anti-stick layer 2 can not only achieve a good non-stick effect and reduce the generation of oil smoke during cooking, but also has high antibacterial ability to ensure the safety and hygiene of food. The armrest assembly 3 on one side provides convenience for use and increases the overall stability and safety of the pot. On the whole, this non-stick pan performs well in terms of performance, quality and user experience.
[0058] See also Figure 1-Figure 7 The base layer 41 is set as a tungsten steel alloy layer, the heat-conducting layer 42 is set as a heat-conducting copper layer, the base-top layer 43 is set as a chromium alloy layer, the cross-sectional shapes of the two ends of the non-stick pan body 1 are set in an arc shape, and the top corners of the non-stick pan body 1 are also set in an arc shape. The antibacterial and anti-stick layer 2 includes a non-stick layer 21, and the non-stick layer 21 is fixedly connected to the top of the base-top layer 43. The top of the non-stick layer 21 is fixedly connected with a composite antibacterial layer 22. The non-stick layer 21 is provided with a nano-diamond coating, and the composite antibacterial layer 22 is set as a titanium ion nano-silver ion composite layer. The base layer 41 is made of a tungsten steel alloy layer with high hardness, which ensures that the pot is sturdy and durable and can effectively resist various external impacts and wear. The heat-conducting layer 42 is a heat-conducting copper layer with excellent conductivity. The thermal performance can make the cookware heat up quickly and evenly, improve cooking efficiency and save energy. The chrome alloy layer of the base top layer 43 further enhances the wear resistance and corrosion resistance of the cookware. The overall cross-sections at both ends and the top corners of the non-stick pan body 1 are both arc-shaped, which is not only beautiful, but also can avoid accidental scratches during use, thereby improving the safety of use. The non-stick layer 21 in the antibacterial and anti-stick layer 2 is a nano-diamond coating with excellent non-stick properties, making the cooking process easier and cleaning more convenient. At the same time, it has high hardness and is not easy to be scratched and damaged. The composite antibacterial layer 22 is a titanium ion nano-silver ion composite layer, which gives the cookware efficient antibacterial ability, ensures the safety and hygiene of food, and brings a healthy cooking experience to users.
[0059] See also Figure 1-Figure 5The armrest assembly 3 includes an armrest frame 31, which is integrally formed and fixedly connected to one side of the non-stick pan body 1. The outer end of the armrest frame 31 is integrally formed and fixedly connected with a handrail rod 32. A wooden handle 33 is installed on the outer side of the handrail rod 32 by bolts. The wooden handle 33 is arranged in a cylindrical shape as a whole. An annular anti-skid groove 34 is evenly spaced on the outer surface of the wooden handle 33. The armrest frame 31 is integrally formed and fixedly connected with the non-stick pan body 1, which ensures the firmness of the connection. There will be no loosening during use, which improves the safety of use. The design of the outer end of the armrest rod 32 is convenient for users to grasp and operate. The wooden handle 33 is cylindrical, conforms to the ergonomic design, and has a comfortable grip. The annular anti-skid grooves 34 evenly spaced on the outer surface increase the friction, which can effectively prevent slipping even when the hands are wet or greasy, thereby improving the stability of operation. Overall, the design of the armrest assembly 3 not only ensures the convenience of use, but also improves the safety and operating experience of the cookware.
[0060] A method for manufacturing a low-smoke, wear-resistant, non-stick pan, comprising the following steps:
[0061] S1: Processing of base layer 41, material preparation, selection of tungsten steel alloy with hardness between HRC80-90, strict control of impurity content below 0.1%, determination of the amount of tungsten steel alloy required according to the size of the pot, use of precision casting or forging process, control of temperature at 1500-1700℃ during casting, so that the tungsten steel alloy is fully melted and flows into the mold to shape the bottom of the pot, forging temperature is controlled at 1200-1400℃, and the density and uniformity of the material are improved through repeated hammering and extrusion to ensure that the bottom of the pot is flat and the thickness meets the design requirements. The thickness range can be 2-4 mm, and the size deviation is controlled within ±0.2 mm;
[0062] S2: Processing of thermal conductive layer 42, high purity copper material is selected, and its thermal conductivity is between 380-400W / (m·K). The thickness of the copper layer is determined according to the size of the pot and design requirements. The specific thickness range is 0.5-1.5 mm. Electroplating or hot dip plating is selected. When electroplating, the current density is controlled at 2-5A / dm 2 The temperature is maintained at 30-50°C, so that the copper ions are uniformly deposited on the tungsten steel alloy base layer 41, and the hot dip plating is carried out at a high temperature of 800-1000°C to ensure that the copper layer and the base layer 41 are tightly bonded, and the bonding strength is greater than 15MPa;
[0063] S3: base and top layer 43 processing, select chromium alloy with hardness between HRC50-60, and then determine the amount of chromium alloy required, the thickness is 0.5-1 mm, welding or spraying can be used during processing, if welding is used, the welding temperature is controlled at 1000-1200℃, the welding current is accurately determined according to the thickness of the chromium alloy and the welding method, and the welding is ensured to be firm. If spraying is used, the spraying pressure is controlled at 0.3-0.5MPa, and the spraying distance is maintained at 150-200mm, so that the chromium alloy is evenly covered on the thermal conductive copper layer, and the chromium alloy layer and the copper layer are firmly bonded, and the bonding strength is greater than 10MPa;
[0064] S4: Non-stick layer 21 processing, select nano diamond powder with a particle size between 10-50 nanometers, and use advanced PVD or CVD methods for coating. If PVD processing is used, the deposition temperature is 300-500℃ and the vacuum degree is 10 -3 -10 -4 Pa, the nano-diamond particles are uniformly deposited on the chromium alloy base top layer 43, the CVD reaction temperature is 800-1000°C, the reaction pressure is 1-10kPa, and a dense nano-diamond coating is generated through chemical reaction, and the coating thickness is controlled to be 0.01-0.05 mm;
[0065] S5: processing the composite antibacterial layer 22, preparing a material with a titanium ion particle size between 50-100 nanometers and a nano silver ion particle size between 10-30 nanometers, and using a coating process to form the composite antibacterial layer 22;
[0066] S6: Processing of the handrail assembly 3, using a stainless steel alloy that matches the material of the cookware, with a hardness between HRC30-40, and forming the handrail frame 31 and the handrail rod 32 in one piece by mold casting or machining, ensuring that the shape is regular and the size meets the design requirements. The connection between the handrail frame 31 and the cookware should be finely processed to ensure a firm connection. Then, natural wood such as oak, walnut, etc. is selected, dried, and anti-corrosion treated, and the wood is processed into a cylindrical shape, and annular anti-slip grooves 34 are provided on the outer surface at equal intervals, with a thickness of 10-20 mm and a length that matches the handrail rod 32;
[0067] S7: Assemble, install the wooden handle 33 on the outside of the handrail 32 by bolts, select bolts of appropriate specifications, strictly control the tightening force, ensure that the installation is firm and there is no looseness, and then integrally form the handrail frame 31 and fix it to one side of the non-stick pan body 1. The connection parts are welded or other reliable connection methods to ensure that the connection is firm and there are no cracks or unevenness;
[0068] S8: Quality inspection, appearance inspection: Carefully inspect the overall appearance of the cookware, including the pot body layer 4 and the armrest assembly 3, to ensure that the surface is smooth, without scratches, dents and other defects, the coating color and glossiness are uniform, the wooden handle 33 surface is flawless, and the annular anti-slip groove 34 is clear and regular; Size inspection: Use calipers, micrometers and other precision tools to measure the size of the cookware, including diameter, depth, and the size of the armrest assembly 3. The diameter deviation is controlled within ±1 mm, the depth deviation is controlled within ±0.5 mm, and the size deviation of the armrest assembly 3 is controlled within a reasonable range; Performance inspection: Test the thermal conductivity of the cookware. The pot is heated to a certain temperature, and the temperature changes at different positions are measured to ensure that the thermal conductivity is greater than 100W / (m·K). A non-stick performance test is conducted to observe the adhesion of food by cooking. It must meet the national standard requirements. An antibacterial performance test is conducted by inoculating bacteria and measuring the changes in the number to ensure that the antibacterial rate is greater than 99%. A strength test is conducted on the handle, and a certain force is applied to check the deformation and firmness. It is required to withstand a tensile force of at least 50N. Overall stability check: Check the connection stability between the pot and the armrest assembly 3. Lift the pot and shake it gently to check if there is any looseness or abnormal sound to ensure that the pot is safe and reliable during use.
[0069] The manufacturing method has the following advantages: first, the use of high-hardness tungsten steel alloy as the base layer 41 ensures the overall strength and durability of the cookware and can effectively resist wear and deformation. Secondly, the heat-conducting layer 42 of high-purity copper ensures good thermal conductivity, so that the cookware can be heated quickly and evenly, saving cooking time and energy consumption. Furthermore, the chromium alloy-based top layer 43 further enhances the wear resistance and corrosion resistance of the cookware. The nano-diamond non-stick layer 21 not only has excellent non-stick properties, but also has high hardness and is not easily scratched and damaged, extending the service life of the cookware. The addition of the composite antibacterial layer 22 gives the cookware efficient antibacterial ability and ensures the safety and hygiene of food. The careful design and processing of the armrest assembly 3 not only ensures the comfort and convenience of use, but also improves the overall stability and safety of the cookware. The strict quality inspection process ensures that each cookware meets high quality standards, allowing consumers to use it with confidence.
[0070] The processing of the composite antibacterial layer 22 includes the following steps:
[0071] 1): Pretreatment of the substrate material, the processed pot body layer 4 is treated, chemical cleaning can be used during the treatment, specifically, ethanol organic solvents, acetone and the like are used to soak the substrate material to remove surface oil stains, and then dilute hydrochloric acid or dilute sulfuric acid is used to remove impurities such as oxides. During the cleaning process, appropriate heating and stirring can be performed to improve the cleaning effect. The cleaning time depends on the degree of contamination of the substrate material, which is 10-30 minutes. Physical cleaning can also be used, specifically, ultrasonic cleaning of the chemically cleaned substrate material, placing the substrate material in an ultrasonic cleaning tank, adding an appropriate amount of distilled water or deionized water cleaning solution, and turning on the ultrasonic cleaning machine. The cleaning time is 10-20 minutes. Ultrasonic cleaning can further remove tiny impurities on the substrate surface to ensure that the surface is flat and clean;
[0072] 2): PVD process, put the pre-treated substrate into the vacuum chamber of the PVD equipment, ensure that the substrate is placed stably and maintains good contact with the electrodes and other components in the chamber, start the vacuum pump, evacuate the vacuum chamber, and gradually reduce the pressure to 10 -3 -10 -5 Pa, this process may take some time, and the specific time depends on the performance of the vacuum pump and the size of the chamber; turn on the sputtering power of the titanium target and the silver target at the same time, and adjust the sputtering power according to the required ratio of titanium ions and nano-silver ions. The power of the titanium target can be set at 3-5kW, and the power of the silver target can be set at 1-3kW. At the same time, introduce an appropriate amount of argon gas into the chamber, and the flow rate is controlled at 20-50sccm. The argon gas forms argon ions under the action of the electric field, bombarding the titanium target and the silver target, so that the titanium ions and silver ions are sputtered out; during the deposition process, the uniformity of the coating is ensured by controlling the rotation speed of the substrate, and the rotation speed of the substrate is set to 5-10rpm. According to the required coating thickness, the deposition time is 30-90 minutes. During the deposition process, the growth of the coating can be observed in real time through the monitoring equipment to adjust the process parameters; after the deposition is completed, turn off the sputtering power and gas supply, wait for the chamber pressure to return to atmospheric pressure, take out the substrate material, and perform quality inspection on the coating, which can be specifically thickness measurement, surface roughness inspection, and adhesion test;
[0073] 3): Preparation of titanium sol, dissolving titanium alkoxide, which can be tetrabutyl titanate Ti(OBu)4, in an ethanol organic solvent at a ratio of 1:10, adding appropriate amounts of water and hydrochloric acid catalyst to the solution, wherein the amount of water added can be set to a molar ratio of tetrabutyl titanate, water and hydrochloric acid of 1:2:0.1, stirring evenly, stirring at room temperature for reaction, the stirring speed can be controlled at 200-400 rpm, the reaction time is 2-4 hours, until a transparent and stable sol is formed, during the reaction, the color and transparency changes of the sol can be observed to determine the progress of the reaction;
[0074] 4): Preparation of silver sol, using silver nitrate as a silver source, dissolving a certain amount of silver nitrate in water, adding an appropriate amount of glucose reducing agent and polyvinyl pyrrolidone PVP protective agent to the solution, the mass ratio of silver nitrate, glucose and PVP can be 1:0.5:1, reacting under heating and stirring conditions, controlling the temperature at 60-80°C, stirring speed at 300-500rpm, reaction time of 1-2 hours, during the reaction process, observing the color change of the solution, when the solution changes from colorless to light yellow or brown, indicating that nanosilver particles have been formed; after completion, cooling to room temperature to obtain silver sol, and performing quality inspection on the silver sol, specifically particle size distribution measurement and stability test;
[0075] 5): Sol-gel composite coating and heat treatment, the prepared titanium sol and silver sol are mixed in a 1:1 ratio, stirred evenly, and the mixed sol is coated on the substrate surface by dipping, spraying or spin coating according to the needs. After coating, the substrate material is placed at room temperature to dry naturally for 1-2 hours, and then the substrate material is placed in an oven for heat treatment, the temperature is controlled at 100-200 ° C, and heated for 30-60 minutes. The heat treatment can gel the sol to form a composite coating; if the thickness of the coating needs to be increased, the coating and heat treatment process can be repeated. Before each coating, it is necessary to ensure that the previous coating has been completely dried and cured, and the composite coating is quality tested, specifically thickness measurement, surface hardness test, and antibacterial performance test;
[0076] The composite antibacterial layer 22 can also be processed by CVD process, specifically, the pretreated substrate is placed in the reaction chamber of the CVD equipment, the reaction chamber door is closed, and a good seal is ensured; the heating system is started to heat the reaction chamber to a suitable reaction temperature. For the composite deposition of titanium and silver, the temperature is controlled between 500-800°C, and the heating process should be carried out slowly to avoid stress or deformation of the substrate material due to too fast temperature change; titanium source and silver source precursor gases, as well as reducing gas, are introduced into the reaction chamber, titanium tetrachloride and silver nitrate are heated and evaporated respectively, and then introduced into the reaction chamber together with hydrogen, and the gas flow is adjusted according to the stoichiometric ratio of the reaction and the deposition rate requirements. The flow rate of titanium tetrachloride can be 10-30ml / min, the flow rate of silver nitrate vapor can be 5-15ml / min, and the flow rate of hydrogen can be 30-60ml / min; during the reaction process, the pressure of the reaction chamber and the residence time of the gas are controlled to allow the precursor to fully react and deposit on the substrate, the pressure of the reaction chamber is controlled at 1-10kPa, and the deposition time is 60-120 minutes to ensure that the composite coating thickness reaches 1-2μm; after the reaction is completed, the heating system and the gas supply are turned off, and after the reaction chamber is cooled to room temperature, the substrate material is taken out and the coating is subjected to quality inspection, specifically component analysis, crystal structure inspection, and surface morphology observation;
[0077] The processing method of the composite antibacterial layer 22 has many advantages. First, through strict pretreatment of the substrate material, the adhesion and uniformity of the subsequent coating are ensured, and the quality and stability of the coating are improved. Secondly, the combination of PVD process and sol-gel method can accurately control the thickness and composition of the coating to achieve good antibacterial properties. The synergistic effect of titanium ions and nano-silver ions gives the coating high-efficiency antibacterial ability, and the antibacterial rate is greater than 99%, which effectively ensures the safety and hygiene of food. Furthermore, the application of CVD process provides another reliable option for the preparation of the coating, which can achieve uniform composite deposition at a higher temperature, and the quality and performance of the coating are more stable. In addition, the choice of multiple coating methods meets the needs of pots of different shapes and sizes and improves the applicability of the process. Finally, strict quality inspection links ensure the quality of each link and ensure the performance and reliability of the final product.
[0078] The working principle of the present invention is as follows: the manufacturing process of this non-stick pan is unique and uses a series of advanced process methods, including precision casting, forging, electroplating, hot dip plating, PVD, CVD and sol-gel method, etc. These exquisite processes ensure that the layers of materials are closely combined and evenly distributed, while also ensuring a high degree of dimensional accuracy;
[0079] During the processing of the base layer 41, the casting and forging temperatures are strictly controlled. By accurately controlling the temperature within a specific range, the tungsten steel alloy base layer 41 exhibits excellent strength and wear resistance. During the cooking process, it can easily withstand various external impacts, laying a solid foundation for the overall stability of the cookware. The heat conductive layer 42 uses electroplating and hot-dip plating processes to firmly combine the high-purity copper material with the base layer 41. This combination not only ensures efficient heat conduction, greatly shortens the cooking time, but also saves energy, which is beneficial to the non-stick layer 21 and the composite anti- Antibacterial layer 22, the use of multiple coating processes ensures the excellent quality and outstanding performance of the coating. For example, the PVD process makes the nano-diamond coating uniform and dense, with excellent non-stick performance. Food is not easy to stick during cooking, and it is convenient and quick to clean. The composite antibacterial layer 22 prepared by the sol-gel method has a significant antibacterial effect, providing a reliable guarantee for the user's cooking environment. In addition, strict quality inspection links are the quality control of the cookware. From the smooth and flawless appearance to the stable and reliable performance, each cookware has undergone strict inspection, providing users with reliable cooking tools;
[0080] The structural design of the pot body layer 4 is scientific and reasonable. It is composed of a base layer 41, a heat conductive layer 42 and a base top layer 43. The materials of each layer are carefully selected to give the pot excellent performance. The base layer 41 is made of tungsten steel alloy with high hardness and few impurities, which lays a solid foundation for the pot and greatly prolongs its service life. The heat conductive layer 42 is made of high-purity copper with high thermal conductivity, which can ensure uniform heat distribution during cooking, avoid local overheating or overcooling, and significantly improve the cooking effect. The chromium alloy of the base top layer 43 has good wear resistance and corrosion resistance, which can effectively protect the surface of the pot and keep it in good condition during long-term use. At the same time, the arc design of the pot body layer 4 is not only beautiful in appearance, but also increases the safety of use. This design avoids the possible harm to the user caused by sharp corners, making the user more at ease during the cooking process. The reasonable design of the overall structure makes the pot excellent in strength, thermal conductivity, durability and other aspects, fully meeting the user's demand for high-quality pots.
[0081] The antibacterial anti-stick layer 2 is composed of a non-stick layer 21 and a composite antibacterial layer 22, and has unique advantages. The non-stick layer 21 adopts a nano-diamond coating with a particle size between 10-50 nanometers. The coating is fine and uniform. During the cooking process, it can prevent food from sticking, which brings great convenience to users and is very convenient and quick to clean. At the same time, the nano-diamond coating also has excellent wear resistance and high temperature resistance, and can maintain a non-stick effect for a long time, ensuring the long-term use performance of the pot. The composite antibacterial layer 22 is composed of titanium ions and nano-silver ions, and is carefully processed through a variety of processes. The antibacterial rate is as high as more than 99%, providing users with a safe and hygienic cooking environment. Among them, nano-silver ions have high-strength antibacterial ability and can effectively inhibit the growth and reproduction of bacteria; and titanium ions not only have antibacterial ability, but also have strong hardness. The two work together to ensure high-strength antibacterial performance while maintaining the use strength of the pot. The existence of the antibacterial anti-stick layer 2 not only greatly improves the use experience of the pot, but also provides a strong guarantee for the health of the family, which is one of the important advantages of this non-stick pan.
[0082] The heat-conducting layer 42 of the non-stick pan is made of high-purity copper material with a thermal conductivity of 380-400W / (m·K), which can efficiently transfer heat and ensure uniform heating during the cooking process. This uniform heating method can avoid local overheating, which is often one of the main reasons for the generation of a large amount of oil smoke. Compared with traditional pots, the improvement of its thermal conductivity allows the temperature in the pot to rise more quickly and evenly, reducing the situation of local high temperature of food causing oil smoke due to uneven temperature.
[0083] The pot body layer 4 is composed of a base layer 41, a heat conductive layer 42 and a base top layer 43. The reasonable design of the overall structure makes the pot excellent in strength, heat conductive performance, durability and other aspects. This structural design can better maintain the stability of the temperature in the pot and avoid excessive temperature fluctuations that cause oil smoke. At the same time, the arc-shaped design is not only beautiful, but also increases the safety of use and helps to reduce the generation of oil smoke to a certain extent. The arc-shaped pot body layer 4 can make the heat more evenly distributed in the pot, reduce the turbulence of the air flow, and thus reduce the generation of oil smoke.
[0084] The non-stick layer 21 uses a nano-diamond coating to prevent food from sticking during the cooking process. When the food is not easy to stick, there is no need to stir and fry too much, thereby reducing the friction between the food and the pot body layer 4 and the excessive concentration of heat, thereby reducing the generation of oil smoke. Moreover, the nano-diamond coating has excellent high temperature resistance and can withstand higher cooking temperatures without producing harmful substances, further reducing the generation of oil smoke.
[0085] Table 1: Performance comparison
[0086]
[0087]
[0088] Table 2: Cooking effect comparison
[0089]
[0090] Table 3: Service life comparison
[0091]
Claims
1. A low-smoke, wear-resistant, non-stick pan, characterized in that: The invention comprises a non-stick pan body (1), wherein the non-stick pan body (1) is composed of an antibacterial anti-stick layer (2) and a pan body layer (4), wherein the antibacterial anti-stick layer (2) is fixedly connected to the outer side of the pan body layer (4), and a handrail assembly (3) is fixedly connected to one side of the non-stick pan body (1); The pot body layer (4) comprises a base layer (41), the base layer (41) is arranged at the bottom of the non-stick body, the top of the base layer (41) is fixedly connected to a heat-conducting layer (42), and the top of the heat-conducting layer (42) is fixedly connected to a base-top layer (43).
2. The low-smoke, wear-resistant, non-stick pan according to claim 1, characterized in that: The base layer (41) is configured as a tungsten steel alloy layer, and the heat-conducting layer (42) is configured as a heat-conducting copper layer.
3. The low-smoke, wear-resistant, non-stick pan according to claim 1, characterized in that: The base and top layers (43) are configured as chrome alloy layers, the cross-sectional shapes of both ends of the non-stick pan body (1) are configured as arc shapes, and the top corners of the non-stick pan body (1) are also configured as arc shapes.
4. The low-smoke, wear-resistant, non-stick pan according to claim 1, characterized in that: The antibacterial anti-sticking layer (2) comprises a non-stick layer (21), wherein the non-stick layer (21) is fixedly connected to the top of the base top layer (43), and the top of the non-stick layer (21) is fixedly connected to a composite antibacterial layer (22).
5. The low-smoke, wear-resistant, non-stick pan according to claim 4, characterized in that: The non-stick layer (21) is provided with a nano-diamond coating, and the composite antibacterial layer (22) is provided with a titanium ion nano-silver ion composite layer.
6. The low-smoke, wear-resistant, non-stick pan according to claim 1, characterized in that: The armrest assembly (3) comprises an armrest frame (31), the armrest frame (31) is integrally formed and fixedly connected to one side of the non-stick pan body (1), the outer end of the armrest frame (31) is integrally formed and fixedly connected to a armrest rod (32), and a wooden handle (33) is mounted on the outer side of the armrest rod (32) via bolts.
7. The low-smoke, wear-resistant, non-stick pan according to claim 6, characterized in that: The wooden handle (33) is arranged in a cylindrical shape as a whole, and annular anti-slip grooves (34) are arranged at equal intervals on the outer surface of the wooden handle (33).
8. A method for manufacturing a low-smoke wear-resistant non-stick pan, applied to a low-smoke wear-resistant non-stick pan according to any one of claims 1 to 7, characterized in that: The steps include: S1: Processing of the base layer (41), material preparation, selecting a tungsten steel alloy with a hardness between HRC80-90, strictly controlling the impurity content below 0.1%, determining the amount of tungsten steel alloy required according to the size of the pot, using precision casting or forging technology, controlling the temperature at 1500-1700°C during casting, so that the tungsten steel alloy is fully melted and flows into the mold to shape the bottom of the pot, and the forging temperature is controlled at 1200-1400°C. Repeated hammering and extrusion improve the density and uniformity of the material to ensure that the bottom of the pot is flat and the thickness meets the design requirements. The thickness range can be 2-4 mm, and the size deviation is controlled within ±0.2 mm; S2: Processing of the heat conducting layer (42), using high purity copper material with a thermal conductivity of 380-400 W / (m·K). The thickness of the copper layer is determined according to the size of the pot and the design requirements. The specific thickness range is 0.5-1.5 mm. Electroplating or hot dip plating is selected. During electroplating, the current density is controlled at 2-5 A / dm 2 The temperature is maintained at 30-50° C., so that the copper ions are uniformly deposited on the tungsten steel alloy base layer (41), and the hot dip plating is carried out at a high temperature of 800-1000° C. to ensure that the copper layer and the base layer (41) are tightly bonded; S3: Processing of the base and top layers (43), selecting a chromium alloy with a hardness between HRC50-60, and determining the required amount of chromium alloy, with a thickness of 0.5-1 mm, and welding or spraying can be used during processing; S4: Processing of the non-stick layer (21), using nano diamond powder with a particle size between 10-50 nanometers, and coating using advanced PVD or CVD methods. When using PVD processing, the deposition temperature is 300-500°C and the vacuum degree is 10 -3 -10 -4 In a high vacuum environment of 1000 kPa, nano-diamond particles are uniformly deposited on a chromium alloy base top layer (43), and a CVD reaction is performed at a temperature of 800-1000° C. and a reaction pressure of 1-10 kPa, so that a dense nano-diamond coating is generated through a chemical reaction, and the coating thickness is controlled to be 0.01-0.05 mm; S5: processing the composite antibacterial layer (22), preparing a material with a titanium ion particle size between 50 and 100 nanometers and a nano silver ion particle size between 10 and 30 nanometers, and forming the composite antibacterial layer (22) by a coating process; S6: Handrail assembly (3) is processed by using a stainless steel alloy that matches the material of the cookware and has a hardness between HRC30-40. The handrail frame (31) and the handrail rod (32) are integrally formed by mold casting or machining to ensure that the shape is regular and the size meets the design requirements. The connection between the handrail frame (31) and the cookware is finely processed to ensure a firm connection. Natural wood such as oak, walnut, etc. is selected and dried and treated with antiseptic treatment. The wood is processed into a cylindrical shape, and annular anti-skid grooves (34) are evenly spaced on the outer surface. The thickness is 10-20 mm and the length matches the handrail rod (32); S7: Assemble, install the wooden handle (33) on the outside of the handrail (32) by bolts, select bolts of appropriate specifications, strictly control the tightening force, ensure that the installation is firm and there is no looseness, and then integrally mold the handrail frame (31) and fix it to one side of the non-stick pan body (1), and use welding to connect the connection parts to ensure that the connection is firm and there are no cracks or unevenness; S8: Quality inspection, appearance inspection: Carefully inspect the overall appearance of the cookware, including the pot body layer (4) and the armrest assembly (3), to ensure that the surface is smooth, without scratches, dents and other defects, the coating color and glossiness are uniform, the wooden handle (33) has no surface defects, and the annular anti-slip groove (34) is clear and regular.
9. The method for manufacturing a smoke-free, wear-resistant, non-stick pan according to claim 8, characterized in that: The processing of the composite antibacterial layer (22) comprises the following steps: 1): Pretreatment of the base material, treating the processed pot body layer (4), during which chemical cleaning can be used, specifically using ethanol organic solvent, acetone, etc. to soak the base material to remove oil stains on the surface, and then using dilute hydrochloric acid or dilute sulfuric acid to remove impurities such as oxides. During the cleaning process, appropriate heating and stirring can be performed to improve the cleaning effect. The cleaning time depends on the degree of contamination of the base material, and is 10-30 minutes. Physical cleaning can also be used, specifically ultrasonic cleaning of the base material after chemical cleaning, placing the base material in an ultrasonic cleaning tank, adding an appropriate amount of distilled water or deionized water cleaning solution, and turning on the ultrasonic cleaning machine. The cleaning time is 10-20 minutes. Ultrasonic cleaning can further remove tiny impurities on the surface of the base to ensure that the surface is flat and clean; 2): PVD process, put the pre-treated substrate into the vacuum chamber of the PVD equipment, ensure that the substrate is placed stably and maintains good contact with the electrodes and other components in the chamber, start the vacuum pump, evacuate the vacuum chamber, and gradually reduce the pressure to 10 -3 -10 -5 Pa, this process may take some time, depending on the performance of the vacuum pump and the size of the chamber; At the same time, the sputtering power of the titanium target and the silver target is turned on, and the sputtering power is adjusted according to the required ratio of titanium ions and nano silver ions. The power of the titanium target can be set at 3-5kW, and the power of the silver target can be set at 1-3kW. At the same time, a proper amount of argon gas is introduced into the chamber, and the flow rate is controlled at 20-50sccm. The argon gas forms argon ions under the action of the electric field, bombarding the titanium target and the silver target, so that the titanium ions and the silver ions are sputtered out; During the deposition process, the uniformity of the coating is ensured by controlling the rotation speed of the substrate. The rotation speed of the substrate is set to 5-10rpm. Depending on the required coating thickness, the deposition time is 30-90 minutes. During the deposition process, the growth of the coating can be observed in real time through monitoring equipment in order to adjust the process parameters. After the deposition is completed, turn off the sputtering power supply and gas supply, wait for the chamber pressure to return to atmospheric pressure, take out the substrate material, and perform quality inspection on the coating, specifically thickness measurement, surface roughness inspection, and adhesion test; 3): Preparation of titanium sol, dissolving titanium alkoxide, which can be tetrabutyl titanate Ti(OBu)4, in an ethanol organic solvent at a ratio of 1:10, adding appropriate amounts of water and hydrochloric acid catalyst to the solution, wherein the amount of water added can be set to a molar ratio of tetrabutyl titanate, water and hydrochloric acid of 1:2:0.1, stirring evenly, stirring at room temperature for reaction, the stirring speed can be controlled at 200-400 rpm, the reaction time is 2-4 hours, until a transparent and stable sol is formed, during the reaction, the color and transparency changes of the sol can be observed to determine the progress of the reaction; 4): Preparation of silver sol, using silver nitrate as a silver source, dissolving a certain amount of silver nitrate in water, adding an appropriate amount of glucose reducing agent and polyvinyl pyrrolidone PVP protective agent to the solution, the mass ratio of silver nitrate, glucose and PVP can be 1:0.5:1, reacting under heating and stirring conditions, controlling the temperature at 60-80°C, stirring speed at 300-500rpm, reaction time of 1-2 hours, during the reaction process, observing the color change of the solution, when the solution changes from colorless to light yellow or brown, indicating that nanosilver particles have been formed; after completion, cooling to room temperature to obtain silver sol, and performing quality inspection on the silver sol, specifically particle size distribution measurement and stability test; 5): Sol-gel composite coating and heat treatment, the prepared titanium sol and silver sol are mixed in a 1:1 ratio, stirred evenly, and the mixed sol is coated on the substrate surface by dipping, spraying or spin coating according to needs. After coating, the substrate material is placed at room temperature to dry naturally for 1-2 hours, and then the substrate material is placed in an oven for heat treatment, the temperature is controlled at 100-200 ° C, and heated for 30-60 minutes. The heat treatment can gel the sol to form a composite coating; if the thickness of the coating needs to be increased, the coating and heat treatment process can be repeated. Before each coating, ensure that the previous coating has been completely dried and cured, and the composite coating is quality inspected, specifically thickness measurement, surface hardness test, and antibacterial performance test.
10. The method for manufacturing a smoke-free, wear-resistant, non-stick pan according to claim 9, characterized in that: The composite antibacterial layer (22) can also be processed by CVD process, specifically, the pre-treated substrate is placed in the reaction chamber of the CVD equipment, and the reaction chamber door is closed to ensure good sealing.
Citation Information
Patent Citations
Novel antibacterial non-stick pan
CN217610679U